The histopathological findings, etiology and prevalence of the dandruff" in vicuñas (Vicugna vicugna mensalis) in the buffer zones of the Pampa Galeras National Reserve - Flores, María (2021)
The objective of this study was to recognize the histopathological findings, to identify the possible agent etiological and to determine the prevalence of the “dandruff" in vicuñas (Vicugna vicugna mensalis) in the buffer zones of the Pampa Galeras National Reserve Bárbara D’achille in Lucanas Rural Community– Ayacucho. Biopsies were taken from the rib region of sixty vicuñas among males and females, ages of youth and adults, which presented “dandruff” in a initial level, obtained from a total of 842 captures vicuñas. The samples were placed in 10% formalin, then were processed by the paraffin inclusion technique and coloured with H. - E., Gram coloration and PAS coloration. The results indicated that the prevalence rate of the dandruff in vicuñas was 9.03%; the most affected population was adult females (13,9%), young female (13,2%) and young male (8,2%). All the skin samples had hyperkeratosis in the córneous layer with parakeratosis (86,7%) and orthokeratosis (13,3%); also, was found the presence of acanthosis in the germinative layer of the epidermis. There was no evidence of fungal infections, parasites and/or bacteria. The histopathological results were compatible with nutritional deficient such as protein, fatty acids, vitamin A, zinc and copper. The most affected group was the vicuñas with the most nutritional requirements, such as vicuñas in growing and reproductive states. These results suggest that over grazzing native pasture is not enough to cover the nutritional requirements of these animals.